The Influence of Individual Morality, Integrity, Catur Purusa Artha, Ineffective Monitoring toward Fraud Tendencies in LPD throughout Tabanan Regency - Komang Sania Widiasari Yumia; I Putu Gede Diatmika; Edy Sujana (Jurnal Ilmiah Akuntansi, 2023)
The operational cessation of LPDs can be attributed to a surge in fraud cases, with LPDs in Tabanan Regency leading in reported incidents from 2018 to 2022. The elevated occurrences of fraud in Tabanan Regency have precipitated a notable decline in the overall health of LPDs. The discernible trend of fraud within these LPDs, resulting in diminished profits and compromised health, necessitates immediate attention to safeguard the sustainability of LPDs in Tabanan Regency. This study aims to investigate the impact of individual morality, integrity, Catur Purusa Artha, and ineffective monitoring on fraudulent tendencies within LPDs in Tabanan Regency. The study encompassed a population of 308 LPDs, involving a total of 1,232 individuals. A systematic sampling approach yielded a representative sample of 204 individuals. The findings of this research reveal that individual morality, integrity, Catur Purusa Artha, and monitoring effectiveness significantly influence the propensity for fraud within LPDs in Tabanan Regency. This underscores the urgency of implementing comprehensive measures to fortify the ethical fabric, financial robustness, and surveillance protocols within LPDs, ensuring their continued viability in Tabanan Regency.